O movimento sindical frente a emergência da cidadania empresarial no contexto da reestruturação produtiva - Rodrigues Netto, Miguel (2019)
This thesis is a theoretical and methodological effort to answer if the perspective of the labor union movement in the State of Mato Grosso, Brazil regarding to the corporate citizenship from the context of the productive restructuring has been a perspective of confrontation or cooptation. It is an exploratory research that seeks to reveal the multiple determinations of the object in a critical perspective of totality. Through a dense literature review, the historical determinants of entrepreneurial citizenship are presented: such as productive restructuring, flexible accumulation through toyotism, the rise of neoliberalism in the world, the counterreformation of the Brazilian State in the 1990 years as well as its mechanisms of domination and legitimation such as green marketing, environmental certifications, the Third Sector, volunteering, telecommuting, organizational culture and also corporate social responsibility. The research considers the historical metamorphoses of labor unionism from its earliest beginnings in Europe, analyzes class struggles, anarchist and communist hegemony, official syndicalism, new syndicalism and result syndicalism concluding with the relationship of labor unions with the governments of the Workers' Political Party in Brazil. Regarding to the State of Mato Grosso, there is a historical overview and the dynamics of economic and social relations with the occupation of the Southern Amazon starting from the 1970 years with the advance of agribusiness and its consequence for the people of that region. The actions of RSC, too union of workers in agriculture, and our federation are our research locus